2013
DOI: 10.2131/jts.38.445
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical evaluation of the neurotoxicity of MPTP and MPP<sup>+</sup> in embryonic and newborn mice

Abstract: -One of the toxicities caused by 1-Methyl-4-phenyl-1, 2, 3, 6-tetrahydropyridine (MPTP) is damage to dopaminergic neurons. When injected into C57BL/6J mice, MPTP penetrates into the brain and is converted to 1-methyl-4-phenylpyridinium (MPP + ) by monoamine oxidase (MAO)-B in astrocytes. MPP + has high affinity for the dopamine transporter (DAT) on dopaminergic neurons, and is taken up into the cell to cause cell death. There have been relatively few researches on the acute MPTP toxicity to embryonic or newbor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…SIRT3 protects a rotenone-induced PD cell model on SH-SY5Y via activation of the liver kinase B1-AMP-activated protein kinase-mTOR pathway [21]. DAT plays an important role in the neurotoxic process [42], and MPP⁺exhibits high affinity to DAT on dopaminergic neurons [18]; thus, MPTP-induced models are most widely used in Parkinsonism research or neuronal protective drug screening among these three neurotoxins. A novel study indicated that silencing PGC-1 alpha in MPTP-treated SH-SY5Y improved cell viability and mitochondrial function [20], presenting a potential therapeutic target in PD drug discovery.…”
Section: Sh-sy5ymentioning
confidence: 99%
“…SIRT3 protects a rotenone-induced PD cell model on SH-SY5Y via activation of the liver kinase B1-AMP-activated protein kinase-mTOR pathway [21]. DAT plays an important role in the neurotoxic process [42], and MPP⁺exhibits high affinity to DAT on dopaminergic neurons [18]; thus, MPTP-induced models are most widely used in Parkinsonism research or neuronal protective drug screening among these three neurotoxins. A novel study indicated that silencing PGC-1 alpha in MPTP-treated SH-SY5Y improved cell viability and mitochondrial function [20], presenting a potential therapeutic target in PD drug discovery.…”
Section: Sh-sy5ymentioning
confidence: 99%
“…1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) is a neurotoxin that inhibits mitochondrial ETC complex I. Following systemic administration, MPTP crosses the blood brain barrier and is converted (in astrocytes) to 1-methyl-4-phenylpyridinium ion (MPP + ) by monoamine oxidase-B [ [9] , [10] , [11] ]. MPP + binds to dopamine transporters on dopaminergic neurons with high affinity, facilitating cellular uptake and resulting in inhibition of ETC complex I, impairment of ATP production and increased oxidative stress and cell death [ [12] , [13] , [14] , [15] ].…”
Section: Introductionmentioning
confidence: 99%
“…Upon uptake in the brain, MPTP is transformed to its active metabolite, 1-methyl-4-phenylpyridinium (MPP + ), by astrocytic monoamine oxidase-B. MPP + has a strong specificity for the dopamine transporter on dopaminergic neurons, where it is taken up and induces cell death [5]. Administration of the toxin MPTP results in nigrostriatal dopaminergic (DA) cell loss of varying degrees that depend on the regimen used [6].…”
Section: Introductionmentioning
confidence: 99%